How different snacks produce a distinct effect in salivary protein composition - Simões, Carla (2022)
Saliva secretion changes in response to different stimulation. Studies performed in animals and humans suggest that dietary constituents may influence saliva composition, although the dynamics of these changes, and how they are specific for each type of food, are little known. The objective of the present study was to access the short-term effects of different foods in salivation and salivary protein composition. Twelve participants were tested for four snacks (yoghurt, bread, apple and walnuts). Non-stimulated saliva was collected before and at 0′, 5′ and 30′ after each snack intake. Flow rate, total protein, alpha-amylase enzymatic activity and salivary protein profile were analyzed. Yoghurt and apple were the snacks resulting in higher salivary changes, with higher increases in flow rate and alpha-amylase activity immediately after intake. The expression levels of immunoglobulin chains decreased after the intake of all snacks, whereas cystatins and one pink band (proline-rich proteins—PRPs) increased only after yoghurt intake. Walnut’s snack was the one resulting in lower changes, probably due to lower amounts eaten. Even so, it resulted in the increase in one PRPs band. In conclusion, changes in saliva composition varies with foods, with variable changes in proteins related to oral food processing and perception